Conceptualising circular economy in Indian agriculture sector: A comprehensive policy approach - Jisha, R H H; Pandian, G A (Plant Science Today, 2025)
Idea of the circular economy in sustainability has received attention worldwide in recent years. Ensuring sustainability in each sector is vital for humans and every other life form on Earth. With 1.4 billion people, India can soon become a global leader in the circular economy and has a huge role to play in promoting sustainability. One of the major sectors where sustainability must be ensured is agriculture. Declining productivity, diminishing soil fertility, limited land resources, massive waste generation and irregular weather patterns due to climate change are major challenges to achieving sustainability in agriculture. India, being an agrarian country and with the key resources for the sustainable agro economy deteriorating day by day, the need for transition into a circular economy becomes inevitable. The present study examines the gaps in existing agricultural policies and explores the possibilities of creating positive change in the agriculture sector. In this setting, this paper proposes the Circular Agro-Economy Policy (CAEP) framework in the Indian context for its implementation to promote sustainable transformation of agriculture in alignment with the Sustainable Development Goals (SDGs). The proposed framework provides a comprehensive approach to mapping the policy environment related to the Indian circular agro economy with recommendations to adopt best practices for circularity in Indian agriculture.